Investigation of Solar Powered Drying System Potential in Niğde Province - Yaşar Serhat Saygılı; Ali Kaan Yetik; Furkan Baş; Burak Şen (Turkish Journal of Agriculture: Food Science and Technology, 2021)
Storage of the foods obtained by plant and animal production is as important as their cultivation. Crops cultivated around the world lose 28-36% of total yield during the process from agricultural land to consumption. With the most of this loss occurs after harvest and harvest, it can be reduced by suitable machines and appropriate methods to be used. Niğde is in third place in the list of cities with the highest apple production in Turkey. In addition, it is seen that the potential of the region to benefit from solar energy is quite high with 8.02 hours of daily sunshine duration and 1550-1800 kWh m-2 total solar radiation values. In line with the information given, Niğde province stands out as an important opportunity for apple drying processes using solar-powered drying methods. In this study, suitable drying methods that can be used for agricultural products in general and methods that can be used in Niğde province have been investigated and with the using the information obtained from previous studies related to the region its examined that the solar drying system and machines that can be developed for the province of Niğde are specified.